Web-based learning: a complementary approach to standard teachnig schemes - Martins, L. (2013)
Web Based Learning is increasingly attracting the interest of several teaching Institutions. It provides mechanisms for improving the conventional learning process, and also allows the opportunity for reaching new students, throughout the world, by just using an Internet connection. This paper describes the objectives of an Europeanfunded project in this area, the features found in current Web-design tools, and our own first experiences within this new teaching scheme.